Stakeholder Collaboration in Managing Edugastro-Tourism Ecosystem - Fitri Abdillah; Sri Fajar Ayuningsih; Antonius Adi (Jurnal Mamangan, 2025)
Edugastro-tourism, which integrates gastronomy and educational experiences, offers opportunities to preserve local food heritage and promote sustainable rural development. This study examines stakeholder collaboration in Hanjeli Tourism Village, located within the Ciletuh-Palabuhanratu UNESCO Global Geopark, Indonesia, where hanjeli (Coix lacryma-jobi L.) serves as the primary gastronomic attraction. A qualitative approach was employed using Participatory Rural Appraisal (PRA) methods—historical mapping, resource mapping, and institutional relationship (Venn) diagrams—with data collected through focus group discussions, in-depth interviews, observations, and documentation. The results identified 18 stakeholders, comprising nine internal and nine external actors. Among them, the women farmers’ group emerged as the most influential stakeholder, closely linked with the daily management of edugastro-tourism, while universities and donor institutions provided strategic contributions through research, innovation, and capacity building. Collaborative practices included developing hanjeli-based food products, establishing homestays, organizing cultural performances, and creating educational tour packages. The findings demonstrate that multi-stakeholder collaboration fosters synergy between tourism, gastronomy, conservation, and food security. Internal stakeholders play a pivotal role in operational activities, while external stakeholders contribute strategically to long-term sustainability. This synergy strengthens governance, diversifies tourism products, and enhances the competitiveness of Hanjeli Tourism Village as a tourism destination.